Integrating UAV Photogrammetry and GIS to Assess Terrace Landscapes in Mountainous Northeastern Türkiye for Sustainable Land Management - Karahan, Ayse; Gokce, Oguz; Demircan, Neslihan; Ozgeris, Mustafa; Karahan, Faris (Mdpi, 2025)
Agricultural terraces are critical landscape elements that promote sustainable rural development by enhancing water retention, mitigating soil erosion, and conserving cultural heritage. In northeastern T & uuml;rkiye, particularly in the mountainous Erikli neighborhood of Uzundere, traditional terraces face growing threats due to land abandonment, topographic fragility, and socio-economic decline. This study applies a spatial-functional assessment framework that integrates UAV-based photogrammetry, GIS analysis, terrain modeling, and DBSCAN clustering to evaluate terrace conditions. UAVs provided high-resolution topographic data, which supported the delineation of terrace boundaries and morphometric classification using an adapted ALPTER model. A combined Terrace Density Index (TDI) and Functional Status Index (FSI) approach identified zones where terraces are structurally intact but functionally degraded. Results indicate that 76.4% of terraces fall within the meso and macro classes, yet 58% show partial or complete degradation. Cohesive terrace clusters are located near settlements, while isolated units in peripheral zones display higher vulnerability. This integrated approach demonstrates the analytical potential of drone-supported spatial diagnostics for monitoring landscape degradation. The method is scalable and adaptable to other terraced regions, offering practical tools for site-specific land use planning, heritage conservation, and resilience-based restoration strategies.
Keywords: agricultural terraces; functional degradation; UAV photogrammetry; GIS spatial analysis; DBSCAN clustering; Terrace Density Index (TDI); Functional Status Index (FSI); landscape fragmentation; sustainable rural planning; terraced heritage landscapes